Nilai Religi Dari Cerita Rakyat Saridin - Abelia Helga Natasya; Aulia Rohmah; Sania Rizka Faiza; Mohammad Kanzunnudin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research uses qualitative research methods to analyze